Information System Security Analysis in the Era of Internet of Things (IoT) - Desi Ratna Sari (Pt. Anagata Sembagi Education, 2024)
The analysis of information system security in the Internet of Things (IoT) era reveals the complexities and challenges associated with ensuring the integrity and security of an increasingly connected infrastructure. The research method used in this study is qualitative research, Data related to information system security in the context of IoT will be collected from various sources, including scientific literature, research reports, and technical documentation and analyzed in-depth literature. Serious threats such as malware, ransomware, and denial of service (DoS) attacks require a proactive and holistic approach in dealing with them. Lack of consistent security standards, device interoperability vulnerabilities, and lack of end-user security awareness are the main focus of efforts to improve security in IoT environments. Cooperation between industry, government, and other stakeholders is needed to develop robust security standards, increase user security awareness, and address interoperability challenges. Through these measures, it is hoped to create a safer and more secure IoT environment, maintaining data integrity and infrastructure security in an increasingly connected and complex era.